2022
DOI: 10.3390/su14148699
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight, Out of Mind: Using Post-Kerbside Organics Treatment Systems to Engage Australian Communities with Pro-Environmental Household Food Waste Behaviours

Abstract: Dealing with the wicked problem of global food waste and loss is a complex and challenging area. In Australia, increased political will has landed the diversion of domestic food waste from landfill squarely at the feet of local government (councils), often requiring significant change to kerbside collections systems. This paper discusses how post-kerbside household food waste treatment systems can encourage pro-environmental behaviours. To achieve this, current food waste literature is examined against kerbsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…Most local governments in Australia provide a behaviour-change program to assist residents to understand and better manage household waste [77]. The causes of organic, particularly food, waste in households are complicated and include multidimensional effects such as social, economic, and individual influences [81]. Understanding residents' approaches to management of household food and garden waste is key to developing collection systems that meet the needs of communities, and effectively delivering programs that assist residents to reduce waste to landfill and increase resource recovery.…”
Section: Behaviour Changementioning
confidence: 99%
“…Most local governments in Australia provide a behaviour-change program to assist residents to understand and better manage household waste [77]. The causes of organic, particularly food, waste in households are complicated and include multidimensional effects such as social, economic, and individual influences [81]. Understanding residents' approaches to management of household food and garden waste is key to developing collection systems that meet the needs of communities, and effectively delivering programs that assist residents to reduce waste to landfill and increase resource recovery.…”
Section: Behaviour Changementioning
confidence: 99%
“…Although some estates have their own collection bins, many still do not have a clear designation where they themselves can send food waste for processing. A study reported using visible kerbside collection bins to engage the community in segregation behaviours [81]. Studies on this area of environmental education may offer more efficient means for continuous reinforcement of green behaviours.…”
mentioning
confidence: 99%